Relationship of childhood obesity associated with family typology and academic performance in schoolchildren - Rosales Córdova, Nadia Celeste; González Pérez, Darely Johany; Padrón Sanchez, Herenia del carmen (Horizonte Sanitario, 2024)
Objective: To analyse the association of childhood obesity associated with family typology and academic performance in schoolchildren in a Family Medical Unit in Tabasco.Material and Methods: Quantitative, observational and analytical study, where anthropometric characteristics were studied, following a method where schoolchildren were classified according to their nutritional status by body mass index. A sample of 162 schoolchildren between 6 and 11 years of age from the family medicine unit no. 45 was studied. A sociodemographic questionnaire was used to determine family characteristics in order to determine family typology. The average grade was used to measure academic performance. A descriptive analysis and an inferential method of variable association were applied.Results: 162 IMSS entitled school children, the classification by gender of the patients, where 56.8 % (n=92) represent the male population studied, while the remaining 43.2 % (n=70) represent the female population, the ages of the patients descriptively, presenting a mean of 9.25 years, mode of 11 years, median of 10 years, standard deviation (SD) of (+/-) 1. 94, variance of 3.771, with a minimum age of 6 and maximum of 11 years.Conclusions: We can infer that there is still a long way to go in managing the necessary strategies for reinforcement by instructing parents to change children's lifestyles in order to have a better quality of life. Keywords: Childhood obesity; Family structure; School performance.